2014
DOI: 10.1039/c4nr04805a
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent carbon nanoparticles derived from natural materials of mango fruit for bio-imaging probes

Abstract: Water soluble fluorescent carbon nanoparticles (FCP) obtained from a single natural source, mango fruit, were developed as unique materials for non-toxic bio-imaging with different colors and particle sizes. The prepared FCPs showed blue (FCP-B), green (FCP-G) and yellow (FCP-Y) fluorescence, derived by the controlled carbonization method. The FCPs demonstrated hydrodynamic diameters of 5-15 nm, holding great promise for clinical applications. The biocompatible FCPs demonstrated great potential in biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…, carbon dots) are promising fluorescent materials, 1–3 which have been applied to various applications, such as bio-imaging tools, 4 photodynamic therapy, 5 chemical sensors, 6 and optoelectronic devices. 7 Recent studies have shown that carbon dots can be prepared from abundant vegetables and fruits such as birch kraft pulp, 8 mango fruit, 9 sweet pepper, 10 grass, 11 and pomelo peel. 12 These natural polymers are composed primarily of polysaccharides, which are rapidly condensed in the presence of strong acids to form carbon dots with a certain degree of homogeneity in their optical properties and dimensions.…”
mentioning
confidence: 99%
“…, carbon dots) are promising fluorescent materials, 1–3 which have been applied to various applications, such as bio-imaging tools, 4 photodynamic therapy, 5 chemical sensors, 6 and optoelectronic devices. 7 Recent studies have shown that carbon dots can be prepared from abundant vegetables and fruits such as birch kraft pulp, 8 mango fruit, 9 sweet pepper, 10 grass, 11 and pomelo peel. 12 These natural polymers are composed primarily of polysaccharides, which are rapidly condensed in the presence of strong acids to form carbon dots with a certain degree of homogeneity in their optical properties and dimensions.…”
mentioning
confidence: 99%
“…S1D, Supporting Information) shows two peaks at 398.5 and 399.9 eV that indicate that nitrogen existed mostly in the form of O=C-N and C-N groups. 26,27 All above results indicated that the surface of the as-prepared N-CDs was passivated by multiple oxygenated and nitrous groups. The UV-vis absorption and PL spectra of the N-CDs are shown in Fig.…”
Section: Characterization Of N-cdsmentioning
confidence: 80%
“…Quinine sulfate (QY 55 (%) at 354 nm excitation) was used as a reference standard to measure quantum yield, adapted from a published report. [6] A particle size histogram was obtained using an ELS-Z size analyzer from Otsuka Electronics Corporation (Osaka, Japan).…”
Section: Characterizationmentioning
confidence: 99%
“…[5] However, for organic compounds, FNPs from condensation reactions as well as carbonization and dehydration systems are the best choice due to their simple manufacturing method. [6] They possess novel properties including water solubility, high stability, biocompatibility, and high optical absorption efficiency with tunable emissions through efficient size dependent excitation. [7][8][9][10] Some reports cite problems when using FNPs such as instability, persistence in the body, and expense of availability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation